ABC transporter function and regulation at the blood-spinal cord barrier - Campos, Christopher R; Schröter, Christian (Journal of cerebral blood flow & metabolism, 2012)
We present here an initial characterization of ATP binding cassette (ABC) transporter function and regulation at the blood-spinal cord barrier. We isolated capillaries from rat spinal cords and studied transport function using a confocal microscopy-based assay and protein expression using western blots. These capillaries exhibited transport function and protein expression of P-glycoprotein (Abcb1), multidrug resistance protein 2 (Mrp2, Abcc2), and breast cancer-related protein (Bcrp, Abcg2). Exposing isolated capillaries to dioxin (activates aryl hydrocarbon receptor) increased transport mediated by all three transporters. Brain and spinal cord capillaries from dioxin-dosed rats exhibited increased P-glycoprotein-mediated transport and increased protein expression for all three ABC transporters. These findings indicate similar ABC transporter expression, function, and regulation at the blood-spinal cord and blood-brain barriers.
Gesehen am 13.04.2018